2005
DOI: 10.1002/rcm.2126
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐residue liquid chromatography/tandem mass spectrometric analysis of beta‐agonists in urine using molecular imprinted polymers

Abstract: Ion suppression, a matrix effect that affects quantitative mass spectrometry, is one of the main problems encountered in liquid chromatography/tandem mass spectrometry. Two different clean-up steps for the multi-residue analysis of beta-agonists in urine were evaluated with respect to minimisation of ion suppression, namely, a mixed-phase solid phase extraction (SPE) column, i.e., clean screen Dau (CSD), and a molecular imprinted polymer (MIP) SPE column. Ion suppression experiments revealed that CSD sample cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
(14 reference statements)
0
26
0
Order By: Relevance
“…Studies of ractopamine residue detection after different treatment schedules in different animal species have been reported by several authors (Elliot et al, 1998;Qiang et al, 2007;Smith & Shelver, 2002;Thompson et al, 2008). Published studies report on tissue residues of ractopamine and its urinary excretion (Antignac et al, 2002;Blanca et al, 2005;Dickson et al, 2005;Moragues & Igualada, 2009;Nielen et al, 2008;Thompson et al, 2008;Van Hoof et al, 2005) and ractopamine residues in hair (Nielen et al, 2008). However, there are little data on the accumulation of ractopamine in pig hair (white or black) as a novel matrix for the control of ractopamine illegal use.…”
Section: Applicability Of Study Resultsmentioning
confidence: 99%
“…Studies of ractopamine residue detection after different treatment schedules in different animal species have been reported by several authors (Elliot et al, 1998;Qiang et al, 2007;Smith & Shelver, 2002;Thompson et al, 2008). Published studies report on tissue residues of ractopamine and its urinary excretion (Antignac et al, 2002;Blanca et al, 2005;Dickson et al, 2005;Moragues & Igualada, 2009;Nielen et al, 2008;Thompson et al, 2008;Van Hoof et al, 2005) and ractopamine residues in hair (Nielen et al, 2008). However, there are little data on the accumulation of ractopamine in pig hair (white or black) as a novel matrix for the control of ractopamine illegal use.…”
Section: Applicability Of Study Resultsmentioning
confidence: 99%
“…Besides that, nearly all described studies using MIPs are methods for the extraction of small groups of compounds [75]. On the other hand, Van Hoof et al [77] developed a multi-residue method for the determination of ␤-agonists in urine using MIPs. In general, it can be concluded that MIPs is a very promising technique, but so far, there are still some features that need to be investigated for the application in the clean-up of f.i.…”
Section: Advanced Extraction and Purification Techniquesmentioning
confidence: 98%
“…There are also reports dealing with the synthesis of MIPs and MS analysis using human specimens for clenbuterol [23], cephalosporin antibiotics [24], β-agonists [25], ropivacaine [26], diazepam and its metabolites [27], and ketamine and its metabolite [28]. Figure 5 shows a fl owchart for the extraction of amphetamines in urine using SupelMIP-Amphetamine cartridges recommended by Sigma-Aldrich [29].…”
Section: Molecularly Imprinted Polymersmentioning
confidence: 99%